2006
DOI: 10.3346/jkms.2006.21.3.577
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans Cell Sarcoma Arising from Langerhans Cell Histiocytosis: A Case Report

Abstract: Langerhans cell sarcoma (LCS) is a neoplastic proliferation of Langerhans cells that have overtly malignant cytologic features. It is a very rare disease and theoretically, it can present de novo or progress from an antecedent Langerhans cell histiocytosis (LCH). However, to our knowledge, LCS arising from an antecedent LCH has not been reported on. We present here a case of LCS arising from a pulmonary LCH. A 34 yr-old man who was a smoker, had a fever and a chronic cough. Computed tomographic (CT) scan revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 14 publications
0
53
0
6
Order By: Relevance
“…Langerhans cell sarcoma may develop de novo or by progression from previous Langerhans cell histiocytosis (LCH) [1,9]. Furthermore, a case of LCS occurring in a patient who underwent liver transplantation was also reported [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Langerhans cell sarcoma may develop de novo or by progression from previous Langerhans cell histiocytosis (LCH) [1,9]. Furthermore, a case of LCS occurring in a patient who underwent liver transplantation was also reported [14].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cell infiltration, consisting of lymphocytes and eosinophil gran- Table I. Summary of the reported cases of Langerhans cell sarcoma [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35] ulocytes, was also found, and isolated mitotic figures were identified ( Fig. 3A and 3B).…”
Section: Case Presentationmentioning
confidence: 95%
“…2,7,15,32 In the present case, the high mitotic rate may be associated with the repeated recurrence after lomustine treatment.…”
mentioning
confidence: 87%
“…In 1984, Wood et al [2] first reported a 71-year-old patient with primary LCS exhibiting a diffusing lung infiltration and multiple skin nodules. In 2006, Jong-Sil Lee et al [4] reported the first case of a 34-year-old patient with pulmonary LCH that progressed into LCS 1 year later. The etiology and pathogenesis of LCS, although not fully understood, is reported to be related to immune abnormalities [1].…”
Section: Discussionmentioning
confidence: 99%